ANALISIS KEMAMPUAN PEMECAHAN MASALAH BERDASARKAN MINAT BELAJAR MATEMATIKA SISWA SMA PEKANBARU PADA MATERI SPLTV - Lusi Wira Aftriyati; Yenita Roza; maimunah maimunah (Department of Mathematics, Hasanuddin University, 2020)
The problem solving abilities of students in learning mathematics are still not well trained, and there are varying degrees of difficulty experienced by students in learning mathematics. Factors that influence the ability to solve problems include interest in learning. This study aims to analyze the ability of problem solving based on students' interest in learning mathematics. This type of research is a descriptive qualitative study, which was conducted at Babussalam Pekanbaru High School with research subjects coming from Class X MIPA 1 selected based on the level of problem solving skills and student interest in learning. Problem solving abilities consist of categories: high, medium, low. Learning interest is categorized as positive and negative interests. Data collection techniques are written tests and non-tests in the form of questionnaire interest in learning and interviews. Based on the research results, the problem solving ability of high category students with positive learning interest is able to meet all indicators of problem solving ability. The problem solving ability of the medium category students with positive learning interest is able to meet the indicators of planning for solving, solving problems, and checking. The problem solving ability of low category students with positive learning interest is only able to meet the indicators of planning a solution, and solving a problem. The ability of problem solving students in the moderate category with negative learning interest is able to meet the indicators of planning for solving, solving problems, and checking.